PREVENTION AND EARLY DETECTION OF CONDYLOMA ACUMINATA IN HUMAN IMMUNODEFICIENCY VIRUS/ACQUIRED IMMUNODEFICIENCY SYNDROME - Dwi Indria Anggraini; Hendra Tarigan Sibero; Muhammad Yusran; Ahmad Fauzi (Jambura Journal of Health Sciences and Research, 2021)
Abstract Human Immunodeficiency Virus infection/Acquired Immunodeficiency Syndrome in Indonesia continues to increase. HIV is a sexually transmitted infection that is often accompanied by condyloma acuminata or genital warts. The incidence of condyloma acuminata in HIV/AIDS patients is reported to vary from 10 to 30% and is associated with low CD4+ levels or at an advanced stage of HIV/AIDS. Condyloma acuminata is caused by the Human Papilloma virus which can develop into malignancy. The purpose of this activity were to increase knowledge about the disease, risk factors, and efforts to prevent condyloma acuminata, as well as to conduct early detection of condyloma acuminate disease in HIV/AIDS patients. The service was carried out through direct education to HIV/AIDS patients who went to the VCT polyclinic at dr. H. Abdul Moeloek. Early detection was done by screening new cases of HIV/AIDS patients. This activity was held for three months and was attended by 112 participants. The results of the activity showed that education could increase the knowledge about the disease, risk factors, and efforts to prevent condyloma acuminata and found 14.3% of condyloma acuminata diseases in the screening program for early detection of disease. The continuity of education and screening program for condyloma